Discussion on "Exact solutions for functionally graded pressure vessels in a uniform magnetic field". (1st January 2016) - Akbari, M.R.; Ghanbari, J.
Abstract: The Paper "Exact solutions for functionally graded pressure vessels in a uniform magnetic field (Dai et al. 2006 )" had several errors with negative impact on the main results. The purpose of the present paper is to discuss the flaws in deriving the formulas and presenting the corrected formulation. Also, the corrected graphs and figures are presented in this paper.